Cr-resistant rhizo- and endophytic bacteria associated with Prosopis juliflora and their potential as phytoremediation enhancing agents in metal-degraded soils - Khan, Muhammad U.; Sessitsch, Angela; Harris, Muhammad; Fatima, Kaneez; Imran, Asma; Arslan, Muhammad; Shabir, Ghulam; Khan, Qaiser M.; Afzal, Muhammad (Frontiers in Plant Science, 2015)
Prosopis juliflora is characterized by distinct and profuse growth even in nutritionally poor soil and environmentally stressed conditions and is believed to harbor some novel heavy metal-resistant bacteria in the rhizosphere and endosphere. This study was performed to isolate and characterize Cr-resistant bacteria from the rhizosphere and endosphere of P. juliflora growing on the tannery effluent contaminated soil. A total of 5 and 21 bacterial strains were isolated from the rhizosphere and endosphere, respectively, could tolerate Cr up to 3000 mg l-1. These isolates also exhibited tolerance to other toxic heavy metals such as, Cd, Cu, Pb and Zn, and high concentration (174 g l-1) of NaCl. Moreover, most of the isolated bacterial strains showed one or more plant growth-promoting activities. The phylogenetic analysis of the 16S rRNA gene indicated a higher and wider range of population of Cr-resistant bacteria in the endosphere than rhizosphere and the predominant species included Bacillus, Staphylococcus and Aerococcus. As far as we know, this is the first report detecting rhizo- and endophytic bacterial population associated with P. juliflora growing on the tannery effluent contaminated soil. The inoculation of three isolates to ryegrass (Lolium multiflorum L.) improved plant growth and heavy metal removal from the tannery effluent contaminated soil suggesting that these bacteria could enhance the establishment of the plant in contaminated soil and also improve the efficiency of phytoremediation of heavy metal-degraded soils.